2016
DOI: 10.1590/0004-282x20160121
|View full text |Cite
|
Sign up to set email alerts
|

Aged Lewis rats exposed to low and moderate doses of rotenone are a good model for studying the process of protein aggregation and its effects upon central nervous system cell physiology

Abstract: ARTICLEAged Lewis rats exposed to low and moderate doses of rotenone are a good model for studying the process of protein aggregation and its effects upon central nervous system cell physiology Ratos Lewis idosos expostos a baixa e moderada doses de rotenona são um bom modelo para estudar o processo de agregação proteica e seus efeitos sobre a fisiologia celular do sistema nervoso central Increase in lifespan is the reality for a number of countries around the world and is frequently associated with a rise in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In our previous study, we showed that exposure to rotenone (1 nM) can induce Aβ and alpha-synuclein aggregation in hippocampal cell cultures, however Tau aggregation required 50% less rotenone to be triggered (0.5 nM), suggesting that rotenone effect upon Tau aggregation is stronger and take place early than Aβ and α-synuclein aggregation. Furthermore, our group also found that in hippocampus of aged Lewis rats, exposed to 2 mg/kg/day of rotenone during 4 weeks, Tau hyperphosphorylation and aggregation is detected in the absence of α-synuclein dysfunction supporting our data ( Almeida et al., 2016 ). In this study, we extend our understanding of Tau pathology analyzing the interplay between oxidative stress and protein degradation pathways during the progression of Tau aggregation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our previous study, we showed that exposure to rotenone (1 nM) can induce Aβ and alpha-synuclein aggregation in hippocampal cell cultures, however Tau aggregation required 50% less rotenone to be triggered (0.5 nM), suggesting that rotenone effect upon Tau aggregation is stronger and take place early than Aβ and α-synuclein aggregation. Furthermore, our group also found that in hippocampus of aged Lewis rats, exposed to 2 mg/kg/day of rotenone during 4 weeks, Tau hyperphosphorylation and aggregation is detected in the absence of α-synuclein dysfunction supporting our data ( Almeida et al., 2016 ). In this study, we extend our understanding of Tau pathology analyzing the interplay between oxidative stress and protein degradation pathways during the progression of Tau aggregation.…”
Section: Discussionsupporting
confidence: 87%
“…Rotenone can also promote Tau hyperphosphorylation and aggregation in a time and concentration- dependent manner in aged rats resembling our experimental protocol for hippocampal cell cultures ( Almeida et al., 2016 ). Then to further expand our findings, we evaluated whether parameters such as H 2 O 2 levels and proteasome activity are also disrupted before the formation of Tau aggregates in the hippocampus of aged rats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most well-known toxins is rotenone, a natural compound used as a pesticide [ 4 ], which can pass through the blood-brain barrier (BBB) [ 5 ]. It causes apoptotic cell death of tyrosine hydroxylase-positive neurons in substantia nigra (SN) of rats [ 6 ]. It induces aggregation of αSN, Aβ, and Tau in rotenone-treated mice, inhibits mitochondrial complex I, and eventually leads to dopaminergic neurodegeneration [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Animal models are reliable to understand the mechanisms of neurodegeneration (Jagmag, Tripathi, Shukla, Maiti, & Khurana, 2015). In this way, rotenone, a high affinity specific inhibitor of mitochondrial NADH dehydrogenase within complex I of the respiratory chain, have been used as a model of PD (Betarbet et al, 2000;Cannon et al, 2009), since it is able to promote α-synuclein aggregation in vitro (Chaves, Melo, Martins, & Ferrari, 2010;Radad, Gille, & Rausch, 2008;Ullrich & Humpel, 2009) and in vivo (Almeida, Silva, D'Unhao, & Ferrari, 2016;Hoglinger et al, 2005). Additionally, rotenone exposure leads to impairment of proteasome activity, oxidative/nitrosative stress, dysfunction of cytoskeleton; reduction of axonal transport and autophagic flux (Almeida, Chaves, et al, 2016;Chaves et al, 2016;Chaves, Melo, D'Unhao, Farizatto, & Ferrari, 2013;Henchcliffe & Beal, 2008), prior to formation of protein aggregates.…”
Section: Introductionmentioning
confidence: 99%